Akibat Hukum bagi Selebgram yang Melakukan Periklanan Menyimpang dari Ketentuan Peraturan Perundang-Undangan - Adi Permana Agung; Ida Ayu Putu Widiati; Ni Made Puspasutari Ujian (Warmadewa Press, 2022)
Selebgram is a promotional service provider that has a role in helping business actors to promote a product or service, the promotion is usually in the form of advertising as a media promotion of products that will be produced and will be sold to the public or consumers with the aim of obtaining profits to be obtained by business actors. However, promotions that are carried out often provide excessive information to attract consumers' interest, sometimes the information presented is not clear and not with facts. The problems raised in this study are what is the legal position of the celebgram as the party that carries out advertising activities on the Instagram social media account, and what are the legal consequences if a celebgram does advertising deviating from the provisions of the legislation. The method used in this research is the normative legal method. In this study, the legal materials used are divided into two, namely primary and secondary. The results of the study indicate that the celebgram is not categorized as a party that has advertisements, this is based on Law No. 32 of 2002 concerning Broadcasting, as well as Law no. 40 of 1999 concerning the Press, despite the fact that the celebgram carries out the advertising activity, with this fact, the celebgram cannot be said to be the press. So that if it is reviewed based on the Press Law, the program has no legal standing and has no legal consequences.